Dopamine-melanin nanoparticles scavenge reactive oxygen and nitrogen species and activate autophagy for osteoarthritis therapy - Zhong, Gang (Nanoscale, 2019)
Anti-oxidative agents hold great potential in osteoarthritis (OA) therapy. However, most radical scavengers have poor biocompatibility and potential cytotoxicity, which limit their applications. Herein we explore dopamine melanin (DM) nanoparticles as a novel scavenger of reactive oxygen species (ROS) and reactive nitrogen species (RNS). DM nanoparticles show low cytotoxicity and a strong ability to sequester a broad range of ROS and RNS, including superoxides, hydroxyl radicals, and peroxynitrite. This translates to excellent anti-inflammatory and chondro-protective effects by inhibiting intracellular ROS and RNS and promoting antioxidant enzyme activities. With an average diameter of 112.5 nm, DM nanoparticles can be intra-articularly (i.a.) injected into an affected joint and retained at the injection site. When tested in vivo in rodent OA models, DM nanoparticles showed diminished inflammatory cytokine release and reduced proteoglycan loss, which in turn slowed down cartilage degradation. Mechanistic studies suggest that DM nanoparticles also enhance autophagy that benefits OA control. In summary, our study suggests DM nanoparticles as a safe and promising therapeutic for OA.